Root Morphology and Rhizosphere Characteristics Are Related to Salt Tolerance of Suaeda salsa and Beta vulgaris L. - Wang, Shoule; Zhao, Zhenyong; Ge, Shaoqing; Peng, Bin; Zhang, Ke; Hu, Mingfang; Mai, Wenxuan; Tian, Changyan (Frontiers in Plant Science, 2021)
Halophytes are capable of resisting salinity, and their root system is the part in direct contact with the saline soil environment. The aim of this study was to compare the responses of root morphology and rhizosphere characteristics to salinity between a halophyte, Suaeda salsa (suaeda), and a glycophyte, Beta vulgaris L. (sugar beet). The soil salt content was set to four levels (0.7%、1.2%、1.7% and 2.7%) by NaCl-treated. We investigated the soil pH, EC, nutrients and soil, plant ion (Na+, Cl-, K+ and Mg2+) concentration to evaluate the rhizospheric processes and salt tolerance of suaeda by the root mat method. The highest biomass was in the 1.2% salt level for suaeda and in the 0.7% salt level for sugar beet. The root length and root surface area of suaeda showed similar trends to biomass, but the root diameter decreased by 11.5% -17.9% with higher salinity. The Na+, Cl-, K+ accumulations in the shoot of suaeda displayed higher than that in sugar beet, while the Mg2+ accumulation was lower in suaeda than that in sugar beet. High salinity resulted in increased pH and EC values in the rhizosphere for suaeda, but lower values of these parameters for sugar beet. Under high salinity, the Olsen-phosphorus content was 0.50 g•kg-1, 0.99 g•kg-1 higher in the rhizosphere than in the non-rhizosphere for suaeda and sugar beet. We concluded that the two species (halophyte, Suaeda salsa (suaeda), and a glycophyte, Beta vulgaris L. (sugar beet)) showed diverse approaches for nutrient absorption under salinity stress. Suaeda altered its root morphology (smaller root diameter, longer roots) under salt stress to increase the root surface area, whilst sugar beet activated rhizosperic processes to take up more nutrients.